Ultrapure Blue Thermally Activated Delayed Fluorescence Molecules: Efficient HOMO-LUMO Separation by the Multiple Resonance Effect - Hatakeyama, Takuji; Shiren, Kazushi; Nakajima, Kiichi; Nomura, Shintaro; Nakatsuka, Soichiro; Kinoshita, Keisuke; Ni, Jingping; Ono, Yohei; Ikuta, Toshiaki (Advanced materials (Weinheim), 2016)
Ultrapure blue‐fluorescent molecules based on thermally activated delayed fluorescence are developed. Organic light‐emitting diode (OLED) devices employing the new emitters exhibit a deep blue emission at 467 nm with a full‐width at half‐maximum of 28 nm, CIE coordinates of (0.12, 0.13), and an internal quantum efficiency of ≈100%, which represent record‐setting performance for blue OLED devices.